Clustering the engagement of Brazilian nurses in political advocacy - Aline Belletti Figueira; Edison Luiz Devos Barlem; Aline Neutzling Brum; Larissa Merino Mattos; Jamila Gere Tomaschewski Barlem; Aline Marcelino Ramos Toescher (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to analyze the level of nurses' engagement in political advocacy by performing cluster analysis. Methods: observational study, with a quantitative approach. A total of 184 nurses working in primary, secondary, and tertiary care in a city in the south of Brazil completed the Policy Advocacy Engagement Scale. Data analysis consisted of descriptive statistics, cluster analysis, analysis of variance, and chi2. The Institutional Review Board approved the study. Results: four differentiated clusters were found according to professional experience, level of healthcare complexity, and unit. The cluster analysis revealed that patient advocacy for community-based obtained the highest mean, indicating that political advocacy is effective in organizational environments and that professional qualification favors greater engagement in political advocacy. Conclusions: the results reveal that nurses play an active role in political advocacy, seeking to promote positive changes in health, especially those working in tertiary care, the nurse group that obtained the highest means.